Altered Relationship Between Parvalbumin and Perineuronal Nets in an Autism Model - Xia, Dan; Li, Li; Yang, Binrang; Zhou, Qiang (Frontiers in Molecular Neuroscience, 2021)
Altered function or presence of inhibitory neurons is documented in autism spectrum disorders (ASD), but the mechanism underlying this alternation is poorly understood. One major subtype of inhibitory neurons altered is the parvalbumin (PV)-containing neurons with reduced density and intensity in ASD patients and model mice. A subpopulation of PV+ neurons expresses perineuronal nets (PNN). To better understand whether the relationship between PV and PNN is altered in ASD, we measured quantitatively the intensities of PV and PNN in single PV+ neurons in the prelimbic prefrontal cortex (PrL-PFC) of a valproic acid (VPA) model of ASD at different ages. We found a decreased PV intensity but increased PNN intensity in VPA mice. The relationship between PV and PNN intensities is altered in VPA mice, likely due to an “abnormal” subpopulation of neurons with an altered PV-PNN relationship. Furthermore, reducing PNN level using in vivo injection of chondroitinase ABC corrects the PV expression in adult VPA mice. We suggest that the interaction between PV and PNN is disrupted in PV+ neurons in VPA mice which may contribute to the pathology in ASD.